Mechanisms of spatial and non-spatial auditory selective attention - Paltoglou, Aspasia Eleni (2009)
Selective attention is a crucial function that encompasses all perceptual modalities and which enables us to focus on the behaviorally relevant information and ignore the rest. The main goal of the thesis is to test well-established hypotheses about the mechanisms of visual selective attention in the auditory domain using behavioral and neuroimaging methods.